ANALISIS PEMBELIAN PRODUK BARU YANG TIDAK DIRENCANAKAN PADA TOKO ONLINE - Wahyu Fitrayanto Nugraha; Sumarsono Sumarsono (Faculty of Economics and Business Universitas Jenderal Soedirman, 2012)
This study analyzed the replication of unplanned purchases at online stores that exist in the kaskus.us fjb seen from the intentions and consumers of psychological factors as a stimulus, a case study at 77 kaskus.us fjb users. This study uses new variable product knowledge, consumer's esteem, consumer's excitement, e-wom, on impulse buying intention and impulse buying behavior. The study revealed that; new product knowledge and consumer's excitement to have a positive relationship to impulse buying intention. Note also that the new product knowledge, consumer's esteem, and word of mouth have a positive relationship to impulse buying behavior. And also found that a positive relationship to impulse buying on impulse buying behavior intention.